Обсессивно-компульсивные явления в патоморфозе простой формы шизофрении - Данилевская, Н. В.; Данілевська, Наталя Володимирівна; Danilevska, N. V. (My University, 2016)
Работа посвящена выявлению и анализу обсессивно-компульсивных явлений в рамках патоморфоза простой формы шизофрении. Установлена доля обсессивно-компульсивных включений в структуре простой формы шизофрении. Рассмотрены особенности динамики обсессивно-компульсивных включений на протяжении развития заболевания. Выделен основной содержательный компонент обсессивных и компульсивных включений в рамках простой формы шизофрении. Aim. To establish the special features of obsessive-compulsive phenomena within pathomorphosis of the simple form of schizophrenia. Materials and methods of research. On the base of MI “Regional clinic psychiatric hospital” of ZRC under condition of the informed consent were examined 58 patients with diagnosis – schizophrenia, simple form (F20.6), among them 31 men and 27 women. The mean age of patients were 42,4±0,82 years old. The duration of disease was 2–25 years. Clinical-anamnestic, clinical-psychopathological, catamnestic and statistic methods were used in the research. In the result of research was observed pathomorphosis of the simple form of schizophrenia. The analysis detected in the clinical picture not only classic manifestations such as autism, decline of energetic potential, emotional deficits and drifting, but also several pathologic syndromes that were earlier considered as not typical for this form of disease. The classic picture of the simple form of schizophrenia realized with especially deficit symptomatology was present in 15,5 % of cases only. In more than ½ of observations in the structure of disease was present the productive symptomatology, the share of obsessive-compulsive inclusions within it was 10,3 %. At the same time obsessive-compulsive phenomena often formed the clinical continuum in the debut of disease, in several cases they were kept during the whole disease and were reliably more often among the patients of male sex. Conclusions. The results of research demonstrate the need for the further study of pathomorphosis of the psychic diseases for elaborating the more qualitative diagnostic criteria of comparing the obsessive-compulsive symptomatology with the different nosological units.
Keywords: психодиагностика; патоморфоз; простая форма; обсессии; schizophrenia; simple form; obsessions; compulsions; pathomorphosis; psychodiagnostics